Cloud-Based Architecture for Production Information Exchange in European Micro-Factory Context - M-Oliveira, Fábio; Rocha, André Dionísio; Alemão, Duarte; Freitas, Nelson; Toshev, Rayko; Södergård, Jani; Tsoniotis, Nikolaos; Argyriou, Charalampos; Papacharalampopoulos, Alexios; Stavropoulos, Panagiotis; Perlo, Pietro; Barata, José (MDPI, 2023)
In a constantly changing world, information stands as one of the most valuable assets for a manufacturing site. However, exchanging information is not a straightforward process among factories, and concerns regarding the trustability and validation of transactions between various stakeholders have emerged within the context of micro-factories. This work presents an architecture designed to enable information exchange among heterogeneous stakeholders, taking advantage of the cloud infrastructure. It was designed to enable the use of several tools, connected through a middleware system deployed on the cloud. To demonstrate the potential of this architecture, a platform was instantiated, and two use cases—designed to accurately represent real manufacturing sites—were implemented.
Keywords: blockchain; cloud; CPPS; ERP; IIoT; Industry 4.0; MES; micro-factories; fi=Tuotantotalous|en=Industrial Management|